Respuesta :

if you mean -x^2 in the beginning there then
x^2 - 3x - 4 = 0
(x-4)(x+1)=0 so x є {-1, 4}
or using the discriminant which is
D=b^2 - 4ac = 9 + 16 = 25
the roots are
(-b+sqrt(D))/(2a) and (-b-sqrt(D))/(2a)
so -1 and 4

if you mean -2*x then
2x=x-4
x=-4

Answer:

x = -4, 1

Step-by-step explanation:

We are given the quadratic equation:

[tex]-x^2+4x=x-4[/tex]

and we are asked to solve for x.

First, we need to get all the terms on one side.

We can achieve this by adding x² and subtracting 4x from both sides:

[tex]0 = x^2 - 4x + x - 4[/tex]

↓ combining like terms

[tex]0 = x^2 + 3x - 4[/tex]

Next, we can factor the right side:

  • Two numbers that add to 3 and multiply to -4:
    4 and -1

[tex]0 = (x+4)(x-1)[/tex]

Finally, we can solve for x using the zero product property:

[tex]x+4 = 0[/tex]   or   [tex]x-1=0[/tex]

[tex]x=-4[/tex]      or   [tex]x=1[/tex]